Assessment of physical performance in field field hockey players in relation to playing position. (Revista horizonte, 2014)
The aim of the research was to evaluate the physical performance of a field-hockey team in relation with the game position. First of all, there were 16 female players, belonging to the first team of the Club Deportivo Alemán in Concepción. The members of the team had more than 2 years of experience in the game and they were in the final period of their season. The team was divided into defenders (n=5), wingers (n=8) and attackers (n=3), goalkeepers were not considered in the investigation. Within the evaluation some aspects like Flexibility, Grip Strength, Counter Movement Jump (CVJ), speed 30m and resistance, were considered when evaluating. In order to prove the meaningful differences between the groups of each variable, it was used ANOVA in a factor and the specificity Tukey test (p